The relationship between occupational exposure to noise and hearing function among paper factory workers / Zuhainy Ahmad Zhaki - Ahmad Zhaki, Zuhainy (2018)
Factories and Machinery (Noise Exposure) Regulation 1989 have always demanded employers to protect their employees from high level noise exposure. However, for the past few years, noise induced hearing loss (NIHL) has been the highest notifiable occupational health issue among Malaysian workers. Thus, this cross-sectional study aims to investigate the relationship between noise exposure levels and hearing function among 56 factory workers who work in different areas within a Selangor-based paper factory. Pure tone audiometry test results were used to determine the hearing levels of the participants. The result shows that the production workers were exposed to higher levels of noise compared to management workers. The comparison of noise exposure level is made by measuring differences between these two groups. An evaluation of the results shows that there is statistically significant difference between the mean noise exposure of production workers and management workers. The mean noise exposure level for production workers is 86.83 dB (A) and for the management workers, it is 72.99 dB (A). The results revealed that there is a statistically significant difference between the mean noise exposure level of production workers (M=86.83, SD=5.60219) and management workers (M=72.99, SD=7.62284), the pvalue is equal to 0.01 which is less than 0.05. Thus, 95% confidence interval, CI was 8.54852 to 18.03148. The p-value is less than 0.05 and CI does not across 0. Based on the results and findings, the noise exposure level shows that equivalent continuous noise levels ranged from 64.1 to 95.2 dB (A). 40% of the participants faced noise exposure above 85 dB (A) and 20% of them have mild hearing loss. In conclusion, production workers are exposed to higher levels of noise, thus exposing them to a higher risk in hearing loss compared to the management workers who are exposed to lower levels of noise thus the risk of developing hearing loss is minimal. Other than occupational noise exposure levels, age, duration of working and type of job were also possible influencing factors in developing hearing loss.